Perceptions and reflections on popular music in Zimbabwe today. - Maguraushe, Wonder; Muranda, Richard (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2016)
In this article we looked at popular music in view of music promoters in the Zimbabwe music industry. Music promoters have found themselves striving for survival in an economy subdued by a scourge of music piracy and a working class with little or no disposable income. The study shows that in the Zimbabwean urban context popular music business is hinged upon profit making. Socio-political and economic factors inform the evolution of popular music over time. From the 1960s to the 1970s popular music was influenced by the emergence of nationalism and the struggle for political independence. From the 1980s to the late1990s celebration of independence from colonialism were central to popular music themes and genres. The years 2000 to 2009 saw the rise of digital technology in the midst of a shrinking economy and a growing dire need for solace through music. The current times have seen the shift towards an increased use of digital technology in recording, production, marketing, sales, and consumption of many genres in popular music. Furthermore, promoters and popular musicians have preferred using real music instruments at live performance shows as opposed to lip syncing. The study recommends that further research be undertaken to find more factors shaping the promotion of popular music in Zimbabwe.